The American retail value proposition : crafting unique experiences at compelling prices - Murray, Kyle B. (Kyle Bayne), 1973- (University of Toronto Press, 2016)
Whether you are an aspiring merchant or an industry veteran, this book's strategic framework will help you build a solid foundation for your business in today's ever-evolving retail marketplace.